(untitled) (Journal of Fatima Jinnah Medical University, 2018)
Objective: To determine the frequency of carotid artery stenosis in non-alcoholic fatty liver disease (NAFLD). Subjects and Methods: This descriptive cross sectional study was carried out on 175 patients with ultrasonic diagnosis of NAFLD. All patients were screened by carotid Doppler scan and in case of a peak systolic velocity greater than 100cm/sec, patient was labeled as having carotid artery stenosis. Results: The mean age of patients of NAFLD was 42.4±9.3 years. Frequency of carotid artery stenosis (CAS) came out about 12.6% among all patients. Hypercholesterolemia was found significantly associated with CAS in NAFLD patients while age, sex and BMI more than 30 kg/m2 was not significantly different in patients with and without carotid artery stenosis. Conclusion: The frequency of CAS is quite high (12.6%) so we should screen all patients of NAFLD for CAS.